2015
DOI: 10.1016/j.watres.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite impregnation effects on the sorbent properties of activated carbons and biochars

Abstract: This paper discusses the sorbent properties of magnetic activated carbons and biochars produced by wet impregnation with iron oxides. The sorbents had magnetic susceptibilities consistent with theoretical predictions for carbon-magnetite composites. The high BET surface areas of the activated carbons were preserved in the synthesis, and enhanced for one low surface area biochar by dissolving carbonates. Magnetization decreased the point of zero charge. Organic compound sorption correlated strongly with BET sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(55 citation statements)
references
References 38 publications
6
46
0
3
Order By: Relevance
“…Carboxylic groups were good for Cu (II) binding as they were bidentate ligands including (SCO) 2 Cu 2+ and (SCO) 2 -Cu(OH) À (Corapcioglu and Huang, 1987). Majority of researchers reported the optimum pH for metal sorption by biochars was less than 7.0 (Tan et al, 2015), while the data varied with the different of sorbent species (Meng et al, 2014;Yang and Jiang, 2014;Han et al, 2015). This was in line with the results of sorption behavior of the modified HLG in this study.…”
supporting
confidence: 89%
“…Carboxylic groups were good for Cu (II) binding as they were bidentate ligands including (SCO) 2 Cu 2+ and (SCO) 2 -Cu(OH) À (Corapcioglu and Huang, 1987). Majority of researchers reported the optimum pH for metal sorption by biochars was less than 7.0 (Tan et al, 2015), while the data varied with the different of sorbent species (Meng et al, 2014;Yang and Jiang, 2014;Han et al, 2015). This was in line with the results of sorption behavior of the modified HLG in this study.…”
supporting
confidence: 89%
“…By contrast AC has reduced surface functionality, as shown by a recent study of these materials (Kwon and Wilson, 2010). The second discriminating feature is the textural properties where AC has a greater BET surface area ($10 3 m 2 /g) compared to the other materials which all are approximately 10 1 m 2 /g (Bismarck et al, 2002;Ayad and Zaghlol, 2012;Sajih et al, 2014;Han et al, 2015). Fig.…”
Section: Resultsmentioning
confidence: 93%
“…7,8 The magnetic modication can improve the adsorption capacity of the hybrid biochar, 7-10 while some reports have found that the efficiency of adsorption by magnetically modied biochar was correlated to its structure. 11,12 In this regard, the magnetic modication has a negative impact on the adsorption capacity of biochar with poorly developed structure.…”
Section: Introductionmentioning
confidence: 99%